Creating a Digital Twin as an Open Source Learning Tool for Mobile Robotics - Magrin, Carlos Eduardo; Conte, Gustavo Del; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
To design a mobile robot, the various stages of development and testing, project costs, and multidisciplinary knowledge discourage students and researchers from starting on such tasks. The digital twin concept, currently addressed in the industry, is related to cyber-physical systems, connecting virtual systems with physical systems. At first, in a mobile robotics project, they can be in the virtual modeling phase, which allows collaborators to test the behavior of the locomotion of the mobile robot, and evaluation many types of sensors, even before the assembly of the real design. In this context, we propose a novel concept of a digital twin mobile robot for use as a tool in mobile robotics projects and encourage undergraduate students and postgraduate students to explore the behavior of a mobile robot at different levels of learning.